Behavior of Adrenal Ectomized Rats in Chloro-Hydroxy Derivatives of Phenothiazine: Synthesis, Testing, and Effects of Chloro-Hydroxy Derivatives of Phenothiazine on Granuloma Growth in Adrenal Ectomized Rats (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Several new Chloro-hydroxy derivatives of phenothiazine such as N10 -[ɐ - (Benzlidene hydrazino)acetyl] 8-chloro 3-hydroxy phenothiazine 2-carboxyalic acid and 2-Substituted aryl, 3- N10 [(acetyl amino)1,3-thiazolidin 4-ones] 8-chloro 3-hydroxy phenothiazine 2-carboxyalic acid have been synthesized and tested for their antimicrobial and anti-inflammatory activities. Structure of the synthesized compounds have been elucidated on the basis of their elemental analysis and spectral data. 8-chloro 3-hydroxy phenothiazine 2-carboxyalic acid produced a significant inhibition of granuloma growth in Carrageenan filter paper granuloma assay in adrenal ectomized rats.